Production of nanopore structure bio-adsorbent from wood waste through a self-sustained carbonization process for landfill leachate treatment - Samsudin, Mohd Hafif; Hassan, Mohd Ali; Mohd Yusoff, Mohd Zulkhairi; Idris, Juferi; Ahmad Farid, Mohammed Abdillah; Lawal, Abu Bakar Abdullahi; Norrrahim, Mohd Nor Faiz; Shirai, Yoshihito (Elsevier, 2022)
The discharge of leachate poses a serious risk to both surface water and groundwater from landfills. As rainwater and moisture seep through waste in landfills, it will release leachate which is high in concentration of organic matter and ammonium nitrogen. Adsorption process using activated carbon was used as one of the tertiary treatment processes in the landfill. This paper presents the utilization of biomass-based adsorbents to substitute the current activated carbon in the landfills. The carbonization process was employed using a 3-tonne self-sustained pool-type reactor, to produce micropores biochar as bio-adsorbent. The carbonization proceeds for 48 h using feedstocks with different initial moisture content of 20% and 40%. The biochar produced had microporosity ranging from 1.8 to 15.4 nm and a surface area of 192.9–231 m2/g. The use of biochar for landfill leachate treatment has shown satisfactory results, with COD, ammoniacal nitrogen, and total Kjeldahl nitrogen removal at 73%, 70%, and 97%, respectively, and heavy metals content value below the Malaysian discharge limits. This exemplifies the potential of biochar as a bio-adsorbent for treating landfill leachate and the feasibility of up-scaling biochar production from wood waste.